The adventures of Beekle The unimaginary friend - Santat, Dan 1975- (SENSEE, 2021)
An imaginary friend waits a long time to be imagined by a child and given a special name, and finally does the unimaginable--he sets out on a quest to find his perfect match in the real world
"This book was made for those with visual impairment. - Spiralbindung. - Titel und Text in Englisch und Braille. - Ursprünglich publiziert: New York [u.a.] Little, Brown & Co., 2014
Keywords: Caldecott Medal / Winner / 1965; Imaginary companions / Juvenile fiction; Friendship / Juvenile fiction; Imaginary playmates / Fiction; Bilderbuch